EFEKTIVITAS DAN KARAKTERISASI FISIK LOSION EKSTRAK ETIL ASETAT DAUN ZODIA (Evodia suaveolens) SEBAGAI REPELAN TERHADAP NYAMUK Aedes aegypti - Aqila Nisa; Emantis Rosa; Sutyarso; Hendri Busman (Shofanah Media Berkah, 2026)
Dengue Hemorrhagic Fever (DHF) has shown an increase in cases and deaths in recent years, reaching 14.6 million cases in 2024 and causing 12,000 deaths. So far, people rely on synthetic repellents containing DEET (N, N-diethyl-meta-toluamide) for prevention. However, long-term use can cause side effects. Therefore, the development of plant-based repellents is needed, such as zodia leaves (E. suaveolens). This study aims to determine the percentage of protective power, determine the EC50 value, and determine the physical properties of ethyl acetate extract lotion from zodia leaves (Evodia suaveolens) through organoleptic, homogeneity, and irritation tests. This study is experimental and descriptive using a Completely Randomized Design (CRD) consisting of 4 test concentrations, namely 0%, 5%, 10%, and 15%. The data obtained were analyzed using one-way ANOVA, followed by LSD test, and probit analysis. The physical properties of ethyl acetate lotion from zodia leaves (Evodia suaveolens) were analyzed descriptively and visually. The results showed that the increase in concentration was directly proportional to the protective power. The mosquito repellent power at concentrations of 5% (18.85%), 10% (33.53%), and 15% (53.27%). The 15% concentration was the highest protective power. Based on probit analysis, the EC50 value was 14.56%. Based on the physical properties of the lotion, it showed that the lotion was homogeneous, had good characteristics, and did not cause irritation.